Framing Robert Mugabe's Death: A De-colonial Analysis. Issue 3 (2nd July 2020) - Santos, Phillip
ABSTRACT: News discourse has been argued to reflect the socio-political and economic interests of which it is a part or serves. It also shows the imbrication of mediation processes with the flows and organisation of power in society. Therefore, by studying news discourse, one can reveal how different societies come to be organised the way they are and their relations to each other. This is a significant task, especially where news media operate in the service of hierarchical social systems that are sustained by maintaining or worsening the circumstances of dominated social groups. In this paper I use de-colonial theory to critically analyse the framing of Robert Mugabe's death by news media in Africa, Britain and the United States. Given the divisive nature of his legacy, and his symbolic association with both the positive and negative aspects of liberation politics, the paper examines and explains the news media's treatment of Robert Mugabe as a political actor and symbol. The analysis shows that arguments for and against Robert Mugabe's legacy can be explained in terms of his posture and practical action in respect of this posture, regarding extant struggles for social justice by former colonial subjects in the Global South.